ANALISIS PENERAPAN PSAK NO. 109 TENTANG AKUNTANSI ZAKAT, INFAQ/SEDEKAH PADA BADAN AMIL ZAKAT NASIONAL KOTA MANADO - Arief, Sartika Wati HS; Manossoh, Hendrik; Alexander, Stanly W. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
The role of BAZNAS in optimizing the potential of zakat in Indonesia is enormous, therefore it is important to pay attention to BAZNAS accounting and accounting activities, the lack of transparency in the Financial Report and the accountability of BAZNAZ will be the trigger of the peoples lack of confidence in distributing zakat and alms in Parties BAZNAS. Zakat funds received and distributed must have a clear and transparent accounting system that is the financial statements must be in accordance with PSAK No. 109 about the accounting of zakat infaq / alms. The objective of this research is to know and apply PSAK No. 109 on the accounting of zakat infak and alms on the financial statements BAZNAS Manado city. Methods of research analysis conducted is descriptive qualitative analysis method. The results of this research indicates that BAZNAS Manado has not applied PSAK No. 109 on its financial statements, and as well as the leadership of BAZNAS shall immediately apply PSAK No. 109 on the accounting of zakat, infaq / alms on the financial statements in BAZNAS Manado because it can provide benefits to the treasury of BAZNAS institutions and give a big effect to the public trust.Keywords : Zakat, Infaq/Alms, PSAK 109, Financial Statements